Semi-fragile watermarking technology based on SVD decomposition and Hadamard transform - Zhi-hong WANG; Hui-fen HUANG; Yu-hong CHANG (网络与信息安全学报)
The semi-fragile watermarking algorithm based on Hadamard transform and SVD decomposition was proposed to distinguish normal image processing operations from malicious tampering.Firstly,the carrier image was SVD decomposed,and Hadamard transform was performed on all image subblocks.The watermark was embedded by quantization method.The algorithm was sensitive to tampering and had good ability to recognize tampering position,and had strong resistance to JPEG compression.